Flowering and tourism in Mallorca and Baix Segre: Two emblematic cases of a tourist-landscape brand image - Alomar Garau, Gabriel; Hidalgo Jiménez, Marc (Geographicalia, 2021)
In this paper, two consolidated cases of landscape-motivated tourism are described: the winter flowering of almond trees in Mallorca (Balearic Islands) and the spring flowering of temperate fruit trees in the Baix Segre sub-region (Catalonia). The objective is to present a synthetic reconstruction of the historical process of formation of these tree crops, and their constitution as a landscape brand image in both regions, as well as their incorporation into the tourist market under the well-known formula of environmental and cultural tourism. In Mallorca, leisure and tourism practices around flowering operate as an alternative to the 'sun and beach' model, while in Baix Segre they constitute their most important contribution to the rural tourism modality. The scope of the flowering and tourism pair has still been little studied, hence it deserves a study that aims to serve as a basis for future works on the subject.